Optical Properties of Nd3+ Doped Phosphate Glasses at 4F3/2 -> 4I11/2 Hypersensitive Transitions - Juniastel Rajagukguk; M. Djamal; R. Hidayat; Suprijadi Suprijadi; A. Amminudin; Yotsakit Ruangtaweep; Jakrapong Kaewkhao (The Journal of Pure and Applied Chemistry Research, 2016)
The lasing transition 4F3/2®4I11/2 for Nd3+ doped phosphate glass centered around 1.05 – 1.07mm is referred as hypersensitive transition. The radiative properties such as effective linewidth (Dleff), radiative transition probability (AR), branching ratio (bR), radiative lifetime (tR), quantum efficiency (h) and stimulated emission cross section have been obtained for several phosphate and fluorophosphate glass contained Nd3+. The experimental and calculated oscillator strength were used to analysis Judd-Ofelt parameters (W2, W4 and W6) also to predict the quality of factor c. The phosphate glass material with the approximately 69P2O5-15Na2O-15K2O-1Nd2O3 composition at 4F3/2 ®4I11/2 transition  is suitable for laser medium. The enhanced radiative transition probability as well as branching ratio and stimulated emission cross section in this glass are 3694 s-1, 52% and 8.67 x10-20 cm2 respectively.  As in commercial laser, the magnitudes of the emission cross section in this study achieved in the range 4.0-5.0 x 10-20 cm2.